(untitled) (Journal of Science Foundation, 2013)
An investigation was carried out on the role of fruits on public health. Amount of nutrition value on different fruits of Bangladesh also examined. Fruits are not only good source of vitamins and minerals but also highly nutritive with anti carcinogenic value. The role of sufficient intake of fruits can prevent many life threatening diseases of human beings like diabetics, blood pressure, heart diseases and cancer. Altogether 39 fruits, the highest water portion 96.6 g was found in black berry and Jamun, and the lowest 4.3 g were found in coconut. The highest total minerals 1.7g was measured in date palm and the lowest 0.1 g was found in orange, black berry and Jamun. The maximum fiber 6.6 mg was found in coconut and the lowest 0.2 g was found in jackfruit and water melon. The highest Calorie 662 Kcal was found in coconut and the lowest 11 Kcal was measured in black berry and Jamun. The highest protein 3.5 g was found in elephants foot apple and the lowest 0.2 g was found in water melon. The highest fat 62.3 g was found in coconut and the lowest 0.1 g was found in jackfruit, ber, elephants foot apple, orange, Bullocks heart/Custard apple, Hogplum, Olive, Aonla, River ebony and Water chestnut. The highest Carbohydrate 33.8 g was found in date palm and the lowest 1.4 g was found in black berry and Jamun. The highest 90 mg was found in Lime and the lowest 0.01g was found in River ebony. The highest amount of Fe 7.9 mg was found in water melon and the lowest 0.2 mg was found in Pummelo. The highest amount of Carotene 8300 ?g was found in mango and the lowest 0 ?g was found in litchi, ber, elephants foot apple, orange, lemon, Bullocks heart/Custard apple, coconut, banana, Aonla and water chestnut. The highest amount of vitamin B-1 0.8 mg was found in elephants foot apple and the lowest 0.01 mg was found in Wax apple, tamarind and Rose apple. The highest amount of vitamin B-2 0.19 mg was found in Burmese grape and the lowest B-2 0.01 mg was found in orange, coconut and olive. The highest amount of vitamin C 463 mg was found in Aonla and Stargareberry, and the lowest 1 mg was found in coconut and water melon. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14633 J. Sci. Foundation, 8(1&2): 111-118, June-December 2010